2014
DOI: 10.14319/ijcto.0203.6
|View full text |Cite
|
Sign up to set email alerts
|

Painless pulsatile mass as first presentation of renal cell carcinoma

Abstract: Renal cell carcinoma rarely presents with typical features of abdominal pain, flank mass and haematuria, and up to 30% of patients present with metastases. We present the case of an 81 year old man who presented with a painless, pulsatile sternal metastasis as an initial presentation of renal cell carcinoma. This case highlights the importance of recognizing even unusual presentations of renal cell carcinoma, and that although sternal metastases are rare, when they do occur there should be a low threshold for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…For example, isolated metastasis to the sternum is considered a rare condition (8). In the literature review, only a few cases of RCC with a solitary sternal metastasis were reported (3,(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…For example, isolated metastasis to the sternum is considered a rare condition (8). In the literature review, only a few cases of RCC with a solitary sternal metastasis were reported (3,(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%